2002
DOI: 10.1167/2.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of the human response to symmetry

Abstract: Symmetry is a highly salient feature of animals, plants, and the constructed environment. Although the perceptual phenomenology of symmetry processing is well understood, little is known about the underlying neural mechanisms. Here we use visual evoked potentials to measure the time course of neural events associated with the extraction of symmetry in random dot fields. We presented sparse random dot patterns that were symmetric about both the vertical and horizontal axes. Symmetric patterns were alternated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 30 publications
6
54
2
Order By: Relevance
“…Bertamini, Makin, and colleagues posit that the SPN is a fairly obligatory electrophysiological response that reflects the processing of symmetric stimuli, and other research has demonstrated that symmetry is an important feature extracted already early in the visual processing stream [16][17][18][19]. In the research by Jacobsen and Höfel, the posterior sustained negativity appeared to be task-dependent and/or driven by spontaneous processes.…”
Section: Discussionmentioning
confidence: 98%
“…Bertamini, Makin, and colleagues posit that the SPN is a fairly obligatory electrophysiological response that reflects the processing of symmetric stimuli, and other research has demonstrated that symmetry is an important feature extracted already early in the visual processing stream [16][17][18][19]. In the research by Jacobsen and Höfel, the posterior sustained negativity appeared to be task-dependent and/or driven by spontaneous processes.…”
Section: Discussionmentioning
confidence: 98%
“…Together these results suggest that when attention is directed toward symmetry, responses increase, but when attention is directed away from symmetry, such as during a color task, responses decrease. This task dependence has not emerged strongly from the EEG literature on symmetry (Höfel and Jacobsen, 2007a, 2007b; Jacobsen, & Höfel, 2003; Makin, Rampone, Pecchinenda, & Bertamini, 2013; Makin et al, 2014; Norcia et al, 2002; Rampone, Makin, & Bertamini, 2014; Wright, Makin, & Bertamini, 2017); however, perhaps because of an increased sensitivity of fMRI to attentional effects, we were able to detect such differences here.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible then, that the additional attentional requirements of these trial‐by‐trial color judgements led to a greater suppression of symmetry‐specific responses to slanted stimuli in the study by Makin et al (2015). It is also of note that the measured EEG symmetry response is not always task dependent and can be similar across tasks, whether people are attending to regularity or some other feature such as the color of the dots (Höfel and Jacobsen, 2007a, 2007b; Jacobsen et al, 2003; Makin et al, 2014, 2013; Norcia et al, 2002; Rampone et al, 2014; Wright et al, 2017). Such task‐dependent differences may therefore only emerge for slanted stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Such symmetrical patterns have been found to be particularly visually salient. For instance, symmetry has clear effects on detection of patterns in random dot fields, contours, and other stimuli (e.g., Machilsen, Pauwels, & Wagemans, 2009;Norcia, Candy, Pettet, Vildavski, & Tyler, 2002;. However, when a symmetrical pattern is tilted relative to the frontal plane, its features in the image projected to the retinae are no longer symmetrical.…”
Section: Symmetrymentioning
confidence: 99%